The Sensitivity of some Types of Citrus Fruits, the role of the Propolis and the Color of Storage Bags in the Development of Green Mold Caused by Fungi Penicillium Digitatium - Hiba Hashim Younes1 , Wa’ad Hamoudi Awad1 , Theyab A. F .Al- Esawee2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
The results of the study indicated that green mold caused by Penicillium digitatium was noticed in all typesof citrus fruits (orange, mandarin, bitter orange, lemon). The most sensitive among these fruits was themandarin with 56.12% infection, followed by orange with 40.18%. On the other hand, the bitter orangeand the lemon showed more resistant to the disease, and the their infection percentages were (32.14% and30.55% respectively. The results indicated that the color of the bags had a great effect on the developmentof the disease where the infection percentages when using light green bags and light yellow bags were(19.68%, 17.24%) respectively. While for the dark black bags, the infection percentage was 13.73%. The useof porpolis in all concentrations (6, 8, 10, 12) g/l did not lessen the size of the infected area compared withcontaminated treatment by pathogen.